Human capital and organisational outcome: mediation and moderation model - Sri Palupi Prabandari; Masyhuri Masyhuri; Setya Ayu Rahmawati (Business, Management and Economics Engineering)
Purpose – This study aims to investigate organisational values as moderators and  playful work design as mediators in the relationship between human capital and organisational outcomes in service industry in Indonesia, utilizing quantitative analysis.